Sistem Pendingin Pada Induced Draft Counter flow Cooling Tower - Muhammad Alfian; La Ode Ahmad Barata; Nining Mahmuda Meliana (Program Pendidikan Vokasi Teknik Mesin, 2022)
There are two factors that determine the rate of heat transfer from hot water to air as a cooling medium, namely the contact time and the surface area between the phases, where to determine the performance of the cooling tower, the performance of the cooling tower needs to be identified. Because of this, research is needed which aims to determine fluid circulation in induced draft counterflow cooling towers and to determine the cooling ability with a standard inlet water temperature of 70oC and a standard outlet water temperature of 27oC. This research uses a structured or quantitative approach method where the research process is carried out by making a design and design of a cooling system which is then identified by measuring and calculating cooling towers. Based on research conducted on the mechanism of fluid circulation in induced draft counterflow cooling towers, it starts with hot water entering the tower being expelled through the nozzle, where the falling water will break and slow down as it passes through the filler. At the same time air enters through the inlet and passes through the filler, hot steam will be attracted along with the air and cold water will fall into the cold water pool. The cooling tower is capable of cooling water from a temperature of 70oC to a standard discharge temperature of 27oC with an average range of 44.38oC and an average approach of -0.67oC and produces an effectiveness value of up to 100% and a maximum heat absorption capacity of up to 225 kW.